Perceived Changes in Ecosystem Services in the Panchase Mountain Ecological Region, Nepal - Adhikari, S.; Baral, H.; Chitale, V.S.; Nitschke, C.R. (MDPI, 2019)
Ecosystem services (ES) are increasingly recognized as a means to facilitate adaption to environmental change. However, the provisions of ES are likely to be impacted by changes in climate and/or changes in land use. In developing countries, where people are typically dependent on these services for their livelihoods, these impacts are of concern; however, very little is known about the changes in provisioning of ES over time. In this study, we assess the perceived changes on ES in the Panchase Mountain Ecological Region of western Nepal. The study area accommodates three distinct ecoregions, ranging from lowland to upland ecosystems and communities. Focus group discussions and key informant interviews were used to collect information on how ES may have changed in the landscape over time. This approach was supported by transect walks, field observations, and secondary sources of information, such as climatic and remote sensing data. Perceived changes on ES in the study region include reduced availability of water, reduced food production, degradation of forest ecosystems, and changes in species compositions. These changes are thought to have impacted other ES, and, in turn, local livelihoods. Management actions that can help local communities foster ES are recommended.